Memanfaatkan Lahan Terbatas Menjadi Kebun yang Produktif untuk Tanaman Hidroponik: Pengabdian - Awari Susanti; Vebrita Sari; Tiar; Meta Rosanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to enhance the knowledge and skills of students and local communities in utilizing limited land as productive gardens through hydroponic methods. The main issue faced by partners is the lack of understanding of hydroponic techniques and limited-space land management, despite their potential to produce healthy and economically valuable vegetables. The activity was carried out through lectures, discussions, video presentations, and hands-on practice in building hydroponic systems. Sixteen participants from various sub-districts attended the training held at Universitas Pahlawan Tuanku Tambusai. The results showed that 100% of training objectives were achieved, participants' knowledge increased significantly, and they successfully understood and applied hydroponic techniques. Therefore, the training effectively empowered students and the community to productively manage limited land and create economic opportunities through hydroponic farming.